Association of catechol-O-methyltransferase gene polymorphisms with treatment response and levodopa-induced complications in Parkinson's disease: A summary of current knowledge - Radojević, Branislava; Jančić, Ivan; Savić, Miroslav; Dragašević-Mišković, Nataša; Kostić, Vladimir (Archives of Pharmacy, 2024)
Catechol-O-methyltransferase (COMT) is one of the cardinal enzymes in the degradation of catecholamines and levodopa. Genetic variants of the COMT gene may affect COMT enzyme activity. The most examined COMT gene polymorphism is the nonsynonymous single nucleotide polymorphism (SNP) in exon 4 (Val108/158Met; rs4680). This highly functional polymorphism is responsible for fourfold variations in enzyme activity and dopamine catabolism. Recent data suggested that even synonymous SNPs of the COMT gene can lead to changes in enzyme activity. Genetically determined COMT activity can affect an individual's response to levodopa therapy and carries the risk of complications from prolonged levodopa use in Parkinson's disease (PD) patients. Identifying at-risk individuals through genetic susceptibility markers could help to prevent the development of levodopa-induced complications in PD.
Keywords: Parkinson's disease; levodopa-induced dyskinesia; hallucinations; COMT gene; single nucleotide polymorphisms; Val158Met (rs4680)